Habitual physical activity is associated with lower fasting and greater glucose-induced GLP-1 response in men. Issue 12 (December 2019) - Janus, Charlotte; Vistisen, Dorte; Amadid, Hanan; Witte, Daniel R; Lauritzen, Torsten; Brage, Søren; Bjerregaard, Anne-Louise; Hansen, Torben; Holst, Jens J; Jørgensen, Marit E; Pedersen, Oluf; Færch, Kristine; et al.
Abstract : Rationale: The hormone glucagon-like peptide-1 (GLP-1) decreases blood glucose and appetite. Greater physical activity (PA) is associated with lower incidence of type 2 diabetes. While acute exercise may increase glucose-induced response of GLP-1, it is unknown how habitual PA affects GLP-1 secretion. We hypothesised that habitual PA associates with greater glucose-induced GLP-1 responses in overweight individuals. Methods: Cross-sectional analysis of habitual PA levels and GLP-1 concentrations in 1326 individuals (mean (s.d. ) age 66 (7) years, BMI 27.1 (4.5) kg/m 2 ) from the ADDITION-PRO cohort. Fasting and oral glucose-stimulated GLP-1 responses were measured using validated radioimmunoassay. PA was measured using 7-day combined accelerometry and heart rate monitoring. From this, energy expenditure (PAEE; kJ/kg/day) and fractions of time spent in activity intensities (h/day) were calculated. Cardiorespiratory fitness (CRF; mL O2 /kg/min) was calculated using step tests. Age-, BMI- and insulin sensitivity-adjusted associations between PA and GLP-1, stratified by sex, were evaluated by linear regression analysis. Results: In 703 men, fasting GLP-1 concentrations were 20% lower (95% CI: −33; −3%, P = 0.02) for every hour of moderate-intensity PA performed. Higher CRF and PAEE were associated with 1–2% lower fasting GLP-1 ( P = 0.01). For every hour of moderate-intensity PA, the glucose-stimulated GLP-1 response was 16% greater at peak 30 min (1; 33%, P rAUC0-30 = 0.04) and 20% greater at full response (3; 40%, P rAUC0-120 = 0.02). No associations were found in women who performed PA 22 min/day vs 32 min/day for men. Conclusion: Moderate-intensity PA is associated with lower fasting and greater glucose-induced GLP-1 responses in overweight men, possibly contributing to improved glucose and appetite regulation with increased habitual PA.